Fabrication of high quality factor lithium niobate double-disk using a femtosecond laser. Issue 1 (2nd January 2017) - Fang, Zhiwei; Yao, Ni; Wang, Min; Lin, Jintian; Zhang, Jianhao; Wu, Rongbo; Qiao, Lingling; Fang, Wei; Lu, Tao; Cheng, Ya
ABSTRACT: We demonstrate fabrication of a high-quality factor lithium niobate double-disk whispering-gallery microcavity using femtosecond laser assisted ion beam milling. Using this method, two vertically stacked 30-µm diameter disks with a 200-nm gap are fabricated. With our device, an optical quality factor as high as 1.35 × 10 5 is demonstrated. Our approach is scalable to fabricate multiple disks on a single chip.